The 7 habits of highly effective teens : the ultimate teenage success guide - Covey, Sean. (New York : Simon & Schuster, 1998)
Being a teenager is both wonderful and challenging. In The 7 Habits of Highly Effective Teens, author Sean Covey applies the timeless principles of the 7 Habits to teens and the tough issues and life-changing decisions they face. In an entertaining style, Covey provides a step-by-step guide to help teens improve self-image, build friendships, resist peer pressure, achieve their goals, get along with their parents, and much more. In addition, this book is stuffed with cartoons, clever ideas, great quotes, and incredible stories about real teens from all over the world. The 7 Habits of Highly Effective Teens will engage teenagers unlike any other book. An indispensable book for teens, as well as parents, grandparents, and any adult who influences young people, The 7 Habits of Highly Effective Teens is destined to become the last word on surviving and thriving as a teen and beyond.
Get in the habit -- Paradigms and principles -- The personal bank account -- Habit 1 : be proactive -- Habit 2 : begin with the end in mind -- Habit 3 : put first things first -- The relationship bank account -- Habit 4 : think win-win -- Habit 5 : seek first to understand, then to be understood -- Habit 6 : synergize -- Habit 7 : sharpen the saw -- Keep hope alive!
"A Fireside book."
Includes index.
Includes bibliographical references and index.
Keywords: Teenagers -- Conduct of life; Success -- Psychological aspects; Teenagers -- Life skills guides; Achievement; Adolescent Psychology; Self Assessment (Psychology); Teenagers -- Conduct of life; Success -- Psychological aspects; Teenagers -- Life skills guides